2015
DOI: 10.1177/0004563215580385
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for specific gravity and creatinine adjustments for urinary steroids and luteinizing hormone concentrations in adolescents

Abstract: 47 Objectives: 48Urinary hormone concentrations are often adjusted to correct for hydration status. We 49 aimed to determine whether first morning void urine hormones in growing 50 adolescents require adjustments and, if so, whether urinary creatinine or specific 51 gravity (SG) are better adjustments. 52 53 Design and Methods: 54The study population was adolescents aged 10.1 to 14.3 years initially who provided 55 fasting morning blood samples at 0 and 12 months (n=343) and first morning urine 56 every three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…originally unconjugated plus deconjugated). The details of the novel urine assays have been published [ 24 ]. Briefly, urine and serum specimens were separated by liquid chromatrography using a Shimadzu Nexera UHPLC system (Shmadzu Scientific Instruments, Columbia, MD).…”
Section: Methodsmentioning
confidence: 99%
“…originally unconjugated plus deconjugated). The details of the novel urine assays have been published [ 24 ]. Briefly, urine and serum specimens were separated by liquid chromatrography using a Shimadzu Nexera UHPLC system (Shmadzu Scientific Instruments, Columbia, MD).…”
Section: Methodsmentioning
confidence: 99%
“…This correction has been implemented in various ways, but in each case the concentration is normalised to a function of the specific gravity (f(SG)) of the urine. One common form of the specific gravity-corrected concentration is (7) where SG reference = 1.020 for Australian or US samples [10,11], 1.015 for Bangladeshi samples [10] and other values are sometimes used [78]. It is often suggested that samples that are too dilute (SG sample < 1.010) or too concentrated (SG sample > 1.030) should be discarded [72], although this is not always done [11] and other limits are sometimes used [74].…”
Section: Specific Gravity-corrected Concentrationmentioning
confidence: 99%
“…One common form of the specific gravity-corrected concentration is (7) where SG reference = 1.020 for Australian or US samples [10,11], 1.015 for Bangladeshi samples [10] and other values are sometimes used [78]. It is often suggested that samples that are too dilute (SG sample < 1.010) or too concentrated (SG sample > 1.030) should be discarded [72], although this is not always done [11] and other limits are sometimes used [74]. For example, Gaines et al [75] reported that 63 or 9 of 417 samples (17%) were too dilute (SG < 1.010) or concentrated (SG > 1.030), respectively (it is clear from the distributions reported by these authors that not all of these samples were also excluded based on u Cr ).…”
Section: Specific Gravity-corrected Concentrationmentioning
confidence: 99%
See 2 more Smart Citations